DOPPLER ASSESSMENT OF SPLANCHNIC ARTERIAL FLOW IN PATIENTS WITH LIVER CIRRHOSIS: CORRELATION WITH NITRIC OXIDE - Glisic, Tijana; Popovic, Dusan; Stojkovic Lalosevic, Milica; Martinov, Jelena; Stojanovic, Marija; Jurisic, Vladimir (Medical Research, 2023)
Introduction/aim: Nitric oxide (NO) is a key mediator who, paradoxically, regulated sinusoidal (intrahepatic) and system/splanchnic circulation. The main goal of this study were measurement of NO, comparison of serum values of NO with flow data in visceral blood vessels of the liver, spleen, kidney and intestine in patients with cirrhosis. Material and methods: This prospective study included 80 patients with liver cirrhosis. Doppler ultrasonography was used to assess flow velocity and resistive index (RI) in the hepatic (HA), right (RRA), and left renal (LRA), splenic (SA) and superior mesenteric artery (SMA). NO concentration was determined using the DetectX® Nitric Oxide colorimetrically detection kit. Results: We find a statistically significant difference in the mean NO value in the group of patients without ascites compared to the ascites group, and also in the group of patients with A stage in relation to the C stage of liver cirrhosis (p <0.05). There is statistically significant negative correlation between NO and diameter, and maximal and minimal velocity in LRA. There is significant positive correlation between NO and minimal velocity in SMA. Conclusions: In this study, we found that patients with liver cirrhosis were exposed to significantly higher RI LRA, RRA, SA and HA. In patients with cirrhosis complicated by ascites and in those with end stage liver disease, the NO level was significantly higher. The concentration of NO has an effect on the diameter and flow rate in the LRA and flow rate in SMA.